A Content Analysis of English Teaching Module Entitled “Practical English” - Farid Munfaati; Mutiatun Nasihah; Ulin Ni’mah; Alfiah Nur Senta; Nurul aini Tsuroyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Providing fruitful instructional material is essential to enhancing the learning process. One of the instructional materials is in the form of a teaching module. This qualitative study aimed at analyzing the content of an English teaching module entitled “Practical English” which was used by non-English majoring students. The evaluation checklist proposed by Chunningsworth was adopted to examine some aspects of the teaching module including the organization of the teaching module, grammar, language skills, listening, speaking, reading, writing, topic and subject content, learner needs, and learning/teaching procedures. In addition, a post-use evaluation was carried out to find the strengths and the shortcomings of the book, which gave an invaluable overview that could be applied to prepare further instructional materials. The results of the present study revealed that the book met most criteria of the evaluation checklist. The teaching module was well organized and presented integrated language skills including listening, speaking, reading, and writing in a meaningful context by providing authentic materials to engage students in realistic contexts. The vocabulary development material in the teaching module, however, was its weak point. The book lacked an index of language terms as well as any clear explanation of vocabulary based on semantic links. In short, the findings of the present study could be valuable for EFL teachers in providing teaching modules as instructional materials to boost successful learning